2021
DOI: 10.20473/jkl.v13i4.2021.250-258
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks Assessment of Heavy Metal from Consumption of Oreochromis Mossambicus and Oreochromis Niloticus in Denpasar, Bali

Abstract: Introduction: Heavy metals in the environment can accumulate in organisms through the food chain process. Previous studies recorded heavy metal concentrations above threshold limits value in Badung river, which warrants monitoring adverse health outcomes due to consuming fish from this river. This research aimed to estimate the potential risk from heavy metals exposure, namely Pb, Cd, Cu, and Cr, due to fish consumption. Methods: Fish samples were limited to Oreochromis Mossambicus and Oreochromis niloticus, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(55 reference statements)
1
1
0
Order By: Relevance
“…The EDIs for lead, mercury, arsenic and copper are below the standards defined by USEPA [ 30 ], which are 2.5 × 10 −3 , 1.0 × 10 −3 , 0.2 × 10 −3 and 10 × 10 −3 mg/kg/day respectively. Similar results were obtained by Dwipayanti et al [ 89 ] on Oreochromis mossanbicus and Oreochromis niloticus , Adegbola et al [ 15 ] on Sarotherodon melanotheron . EDI reflects daily exposure to the heavy metal and is used to prevent any harmful effects on human health.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The EDIs for lead, mercury, arsenic and copper are below the standards defined by USEPA [ 30 ], which are 2.5 × 10 −3 , 1.0 × 10 −3 , 0.2 × 10 −3 and 10 × 10 −3 mg/kg/day respectively. Similar results were obtained by Dwipayanti et al [ 89 ] on Oreochromis mossanbicus and Oreochromis niloticus , Adegbola et al [ 15 ] on Sarotherodon melanotheron . EDI reflects daily exposure to the heavy metal and is used to prevent any harmful effects on human health.…”
Section: Resultssupporting
confidence: 89%
“…Magna et al [ 16 ] obtained THQ and HI values below 1 in O. niloticus from the Volta Bassin of Ghana. THQ values lower than 1 and HI values higher than 1 were obtained by Dwipayanti et al [ 89 ] on O. mossanbicus and O. niloticus . Adegbola et al [ 15 ] reported TQH and HI values greater than 1 on Sarotherodon melanotheron .…”
Section: Resultsmentioning
confidence: 84%
“…Hasil penelitian menunjukkan bahwa seluruh responden telah memiliki jamban leher angsa. Hasil penelitian ini sesuai dengan penelitian 9 , tidak sejalan dengan hasil penelitian 10 . Tipe jamban dengan bentuk leher angsa merupakan tipe yang memenuhhi persyaratam sanitasi.…”
Section: Aspek Lingkunganunclassified